2010
DOI: 10.1074/jbc.m110.143164
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex II Prevents Hypoxic but Not Calcium- and Proapoptotic Bcl-2 Protein-induced Mitochondrial Membrane Potential Loss

Abstract: Mitochondrial membrane potential loss has severe bioenergetic consequences and contributes to many human diseases including myocardial infarction, stroke, cancer, and neurodegeneration. However, despite its prominence and importance in cellular energy production, the basic mechanism whereby the mitochondrial membrane potential is established remains unclear. Our studies elucidate that complex II-driven electron flow is the primary means by which the mitochondrial membrane is polarized under hypoxic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 55 publications
6
20
0
Order By: Relevance
“…In mitochondria from hypoxic endothelial cells, the considerably elevated protein expression and activity of complex II contribute to an increase in mΔΨ and succinate-sustained mROS formation mainly through increased reverse electron transport. It has been previously reported that in endothelial cells, complex II-driven electron flow is the primary means by which the mitochondrial membrane is polarized under hypoxic conditions [10]. Another interesting finding from this study is that, in mitochondria from hypoxic endothelial cells, a reduction of expression and maximal malate-sustained activity of complex I was accompanied by an increase in oxidation of other weaker than malate NAD-linked substrates α-ketoglutarate or isocitrate.…”
Section: Discussionsupporting
confidence: 66%
“…In mitochondria from hypoxic endothelial cells, the considerably elevated protein expression and activity of complex II contribute to an increase in mΔΨ and succinate-sustained mROS formation mainly through increased reverse electron transport. It has been previously reported that in endothelial cells, complex II-driven electron flow is the primary means by which the mitochondrial membrane is polarized under hypoxic conditions [10]. Another interesting finding from this study is that, in mitochondria from hypoxic endothelial cells, a reduction of expression and maximal malate-sustained activity of complex I was accompanied by an increase in oxidation of other weaker than malate NAD-linked substrates α-ketoglutarate or isocitrate.…”
Section: Discussionsupporting
confidence: 66%
“…This, in turn, stabilizes the ODD domain of the HIF1␣, which in the ODD-GFP construct regulates the stability of GFP. Because we did not observe GFP fluorescence in HCT116 ODD-GFP cells exposed to MitoVE 11 S in less than 6 h (data not shown), whereas significant ROS accumulation occurred within relatively short periods, the pseudohypoxic state is probably secondary to the importance of ROS in promoting the onset of apoptosis in cancer cells exposed to MitoVE 11 S. To corroborate this premise, using live confocal microscopy and cells transfected with the pHyPer-dMito plasmid coding for the redox sensor OxyR (65), we observed generation of ROS in cancer cells as early as in 5 min following the addition of MitoVE 11 S. 3 This further supports the primary role of the CII UbQ-binding site in the molecular action of the agent and is consistent with the notion that inhibition of CII can result in HIF1␣ stabilization (31,32,66,67).…”
Section: Discussionsupporting
confidence: 62%
“…To determine cytoprotective effects of VEGF-B 167 , neonatal rat cardiomyocytes were isolated and cultured with reactive oxygen specie (ROS) production measured as previously described (19,21,22). They were exposed to VEGF-B 167 , VEGF-A, VEGF-E, and placental growth factor (PlGF) in the absence or in the presence of angiotensin II or norepinephrine (50 M −6 ) (Online Appendix).…”
Section: Methodsmentioning
confidence: 99%